Analisis Deskriptif Rasio Profitabilitas dan Solvabilitas Sebelum dan Sesudah Penerapan PSAK 116 - Winny Salma Nur Azizah; Sintikhe Ruth Dere (Jurnal Sosial Teknologi, 2026)
The implementation of PSAK 116 on lease has brought changes in the presentation of the company's financial statements, especially related to the recognition of assets of use rights and lease liabilities. These changes have implications for the presentation of financial ratios used to assess company performance. This study aims to describe and compare changes in the company's financial ratios before and after the implementation of PSAK 116. This study uses a quantitative approach with a type of comparative descriptive research. The data used is secondary data obtained from the financial statements of the sample company. The analysis was carried out using descriptive statistics and a comparison of the average value of financial ratios in the period before and after the implementation of PSAK 116. The financial ratios analyzed include Return on Assets (ROA), Return on Equity (ROE), Debt to Assets Ratio (DAR), and Debt to Equity Ratio (DER). The results of the study show that there are changes in the company's profitability and solvency ratios after the implementation of PSAK 116, with a pattern of change that varies between companies. Some companies have increased ratios, while others show fluctuations or decreases in the value of ratios. The change reflects an adjustment in the presentation of the structure of assets, liabilities, and equity in the company's financial statements. This study provides an overview that changes in financial ratios after the implementation of PSAK 116 need to be understood as a consequence of changes in accounting standards. Therefore, users of financial statements are expected to be able to interpret financial ratios by considering the context of the implementation of PSAK 116.